Android Based Minang Language Using UCD Method (User Centered Design): Tour Guide Application - Aysyah Rengganis; Sumitro Sarkum; Ibu Rasyid Munthe; Iwan Purnama (ISB Atma Luhur, 2018)
UCD (User Centered Design) is a design philosophy of putting users at the center of a system development process. The difficulties experienced by the tourists who visited West Sumatra during traveling is in communicating which can be helped by using UCD method. The approach using UCD method has been supported by various techniques, methods, tools, procedures and processes that help to design more user-centered applications. In the UCD method the user is at the level of design sophistication of all interfaces used based on the guide application. In making the application, the tool used in designing tourist guide application design is using Unified Modeling Language (UML). Data excavation is done by interview and observation to the end user, and library study. Tour guide application built using eclipse with SQLite database storage media. The result of this design is expected to provide convenience to the tourists in making tourism visits to West Sumatra.